Magnetotransport measurements on Bi2Te3 nanowires electrodeposited in etched ion-track membranes. (May 2019) - Krieg, J.; Giraud, R.; Funke, H.; Dufouleur, J.; Escoffier, Walter; Trautmann, C.; Toimil-Molares, M.E.
Abstract: We report on the magneto-transport properties of individual Bi2 Te3 nanowires with diameters ranging from 25 nm to 120 nm fabricated by electrodeposition in etched ion-track membranes. The metallic behavior of all nanowires is typical for highly-degenerate semiconductors and the weak temperature dependence of the resistivity suggests a weak electron-phonon coupling, as expected for topological surface states with quantum confinement. The diameter dependence of the resistivity further confirms the quasi-ballistic nature of charge carriers, in agreement with the reduction of the number of surface conductance channels in disordered quantum wires with a stronger quantum confinement. Although the bulk conductance is not negligible, both the transport length of bulk carriers and their electrostatic screening length remain shorter than the nanowire diameter, probably leading to a small contribution to the resistivity change. Quantum transport measurements give further evidence of finite-size effects, as shown by the weak anti-localization correction to the conductance, below 15K, and reveal the coexistence of surface Aharonov-Bohm oscillations and bulk universal conductance fluctuations, below 5K. Graphical abstract: Image 1